2018
DOI: 10.1073/pnas.1810211115
|View full text |Cite
|
Sign up to set email alerts
|

Critical computational analysis illuminates the reductive-elimination mechanism that activates nitrogenase for N 2 reduction

Abstract: Recent spectroscopic, kinetic, photophysical, and thermodynamic measurements show activation of nitrogenase for N 2 → 2NH 3 reduction involves the reductive elimination (re) of H 2 from two [Fe-H-Fe] bridging hydrides bound to the catalytic [7Fe-9S-Mo-Chomocitrate] FeMo-cofactor (FeMo-co). These studies rationalize the Lowe-Thorneley kinetic scheme's proposal of mechanistically obligatory formation of one H 2 for each N 2 reduced. They also provide an overall framework for understanding the mechanism of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
246
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(263 citation statements)
references
References 68 publications
14
246
3
Order By: Relevance
“…This energetic analysis suggests that models j-o are the most viable models for the E 4 state (at the TPSSh-QM/MM level). Open sulde-bridge models like j-o were not considered in the study by Cao et al 27 but some open-sulde bridge models were discussed by Raugei et al 24 and were found to be similar in energy as model e, which, however, is not in agreement with our results. We attribute this disagreement to different modelling aspects, i.e.…”
Section: A Computational Modelling Of the E 4 Statecontrasting
confidence: 97%
See 3 more Smart Citations
“…This energetic analysis suggests that models j-o are the most viable models for the E 4 state (at the TPSSh-QM/MM level). Open sulde-bridge models like j-o were not considered in the study by Cao et al 27 but some open-sulde bridge models were discussed by Raugei et al 24 and were found to be similar in energy as model e, which, however, is not in agreement with our results. We attribute this disagreement to different modelling aspects, i.e.…”
Section: A Computational Modelling Of the E 4 Statecontrasting
confidence: 97%
“…All models that we consider in this study were structurally optimized at the same QM/MM level of theory that we have previously used to describe the resting state E 0 and we considered multiple broken-symmetry states for each model. As recently discussed by Raugei et al, 24 the protein environment and the quality of the computational model can make a surprisingly large difference regarding the relative stability of an E 4 isomer. Raugei et al demonstrated e.g.…”
Section: A Computational Modelling Of the E 4 Statementioning
confidence: 95%
See 2 more Smart Citations
“…in clusters of Mn atoms in Photosystem II (PSII) or Fe and Mo atoms in nitrogenases. [4][5][6][7] Furthermore, the coordination of small molecules to single metal ions is an important motif in drug design, 8 and the correlations exhibited in the copper oxide layers of cuprate materials play a central role in the phenomenon of high-temperature superconductivity. 9,10 Ab initio modeling has the potential to yield essential insights into these transition metal systems.…”
Section: Introductionmentioning
confidence: 99%